PENDIDIKAN KRISTEN DALAM KELUARGA MENURUT HORACE BUSHNELL DAN IMPLEMENTASINYA DI GEREJA KIBAID JEMAAT SALUBARANI - Allo Rundun, Irna (SEKOLAH TINGGI TEOLOGI KIBAID MAKALE, 2022)
Abstract. This research is motivated by the fact that there is a lack of attention to Christian education in the family at the KIBAID Church of the Salubarani Congregation. The purpose of this study is to determine the factors that cause families in the Salubarani Congregation not to maximize the implementation of Christian education in the family. This research was developed using a descriptive-library method by placing the families of members of the Salubarani KIBAID Church as the object of research. The results of this study indicate that Christian education is not optimal in the families of the Salubarani Congregation due to the busy work factor which is accompanied by a lack of awareness of the importance of Christian education in the family, as well as the lack of qualifications of faith and Christian character in the parents in the families of the Salubarani Congregation. Abstrak. Penelitian ini dilatarbelakangi fakta kurangnya perhatian pada pendidikan Kristen dalam keluarga di Gereja KIBAID Jemaat Salubarani. Tujuan penelitian ini ialah untuk mengetahui faktor-faktor yang menyebabkan keluarga-keluarga di Jemaat Salubarani tidak memaksimalkan pelaksanaan pendidikan Kristen dalam keluarga. Penelitian ini dikembangkan dengan metode deskriptif-kepustakaan dengan menempatkan keluarga-keluarga anggota Gereja KIBAID Jemaat Salubarani sebagai objek penelitian. Adapun hasil penelitian ini menunjukkan bahwa tidak maksimalnya pendidikan Kristen dalam keluarga-keluarga Jemaat Salubarani dikarenakan faktor kesibukan bekerja yang dibarengi dengan kurangnya kesadaran akan pentingnya pendidikan Kristen dalam keluarga, serta kurangnya kualifikasi iman dan karakter kristiani pada diri para orang tua dalam keluarga-keluarga Jemaat Salubarani.